Implementation of Billboard Implementation Policy in Pekanbaru City - Monica Rosiana Sitorus; Hasim As’ari (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Pekanbaru City is a city that is categorized as a metropolitan city, as Pekanbaru is closely related to the spread of billboards. Billboards are one of the mediums for entrepreneurs in Pekanbaru. However, with the rise of billboards in Metropolitan Cities such as Pekanbaru, there are still many who violate regulations. This study aims to analyze the implementation of billboard implementation policies in Pekanbaru City and its constraints. The theory used is Thomas B Smith's policy implementation theory, namely there are 4 indicators: the idealized policy, target group, implementing organization, and environmental factors. This research uses a type of qualitative research that is descriptive. The results of the study found that the implementation of the billboard implementation policy in Pekanbaru City has not been carried out in accordance with Mayor Regulation Number 24 of 2013 which has been amended into Pekanbaru Mayor Regulation Number 50 of 2021 concerning the implementation of billboards. The obstacles faced when implementing this policy are unprofessional implementors, socialization does not reach the target group and lack of compliance of billboard organizers.